1990
DOI: 10.1021/ja00171a037
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of (.eta.5-C5H5)Rh(CO)2 in phosphine solutions: evidence for an associative photosubstitution mechanism

Abstract: Over the past few years there has been much interest in the photochemistry of (i/5-C5R5)ML2 and (r)5-C5R5)ML(H)2 ( = Rh, Ir; R = H, CH3; L = CO, PR3, olefin) complexes leading to intermolecular activation of hydrocarbon C-H bonds.1 Extensive matrix isolation, flash photolysis, and low-temperature solution studies have been performed on these systems, and they indicate that their C-H activation and photosubstitutional reactions proceed initially via ligand dissociation to yield a 16electron species.2 Recently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…5. According to some availably experimental observations, 23,29,30 Harris and coworkers reported that the irradiation of light to Rh-S 0 -Rea is 295 nm (¼ 96.9 kcal mol À1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…5. According to some availably experimental observations, 23,29,30 Harris and coworkers reported that the irradiation of light to Rh-S 0 -Rea is 295 nm (¼ 96.9 kcal mol À1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, this nding has been conrmed by the experimental observations, in which the photodecarbonyl reaction of Rh-S 0 -Rea nally occurs a singlet 16-electron organometallic h 5 -CpRh(CO) species. 23,29,30 Subsequently, Rh-S 0 -Int interacts with Si(H)Me 3 to form a singlet precursor complex (Rh-S 0 -Cpx), whose energy is Fig. 6 Energy profiles for the photo-oxidative-addition reactions for h 5 -CpIr(CO) 2 (Ir-S 0 -Rea).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations